Electronic structure and properties of layered gallium telluride - Shenoy, U. Sandhya; Gupta, Uttam; Narang, Deepa S.; Late, Dattatray J.; Waghmare, Umesh V.; Rao, C. N. R. (Chemical Physics Letters, 2016)
Layer-dependent electronic structure and properties of gallium monochalcogenides, GaX where X=S, Se, Te, have been investigated using first-principles calculations based on various functionals, with a motivation to assess their use in photocatalytic water splitting. Since hydrogen evolution by water splitting using visible light provides a promising way for solar energy conversion, both theoretical and experimental studies have been carried out on the photochemical hydrogen evolution by GaTe. We also present the Raman spectra of GaTe examined by both theory and experiment. (C) 2016 Elsevier B.V. All rights reserved.